The visual culture of Meiji Japan: negotiating the transition to modernity - Zohar, Ayelet; Miller, Alison J. (Routledge, Taylor & Francis Group, 2022)
Japan as Far West : An Allegorical Reading of the Katakana Space / Michio Hayashi -- Medievalism and Militarism in Imperial Japan / Oleg Benesch -- Colors of Empire : Watercolor in Meiji Japan / Chinghsin Wu.
Includes bibliographical references and index
"... conference, titled "The West in Japanese Imagination/Japan in Western Imagination: 150 Years to the Meiji Restoration", held in December 2018 at Tel Aviv University ..." (Acknowledgements)
Keywords: Japan; Westliche Welt; Konferenzschrift -- 2018 -- Tel Aviv